On Project of School Spelling Dictionary of Yakut Language - N. M. Vasilyeva (Научный диалог, 2019)
The project of “School spelling dictionary of the Yakut language” for secondary school students is considered. The relevance of the study is linked with the approval in 2015 in the Republic of Sakha (Yakutia) of new spelling and punctuation rules of the Yakut language, which in turn is determined by the decrease in the prestige of literacy in the eyes of young speakers of the Yakut language. It is noted that in the same year, taking into account the innovations, “Spelling dictionary of the Yakut language” was reissued, on the basis of which the school version of the spelling dictionary is developed. It is indicated that the need for the introduction of the latter is due to the school tasks of studying spelling, a large spelling dictionary being beyond them. The author substantiates the necessity of compiling a dictionary focused on the student, describes its concept and objectives, features of content and structure. The features of inclusion in the school dictionary of various lexical units, including obsolete words, dialect words, some terms, homonyms, proper names, are shown. The author demonstrates the system of marks accepted in the dictionary and the conditions for inclusion of a meaning in the dictionary entry. It is noted that the words borrowed from the Russian language are represented in the new dictionary phonetically, differently than it was accepted by tradition in the Soviet period.